STUDI KASUS PTERIGIUM PADA PEKERJA ADMINISTRASI PERUSAHAN PERTAMBANGAN - Melani Gozali; Adriani Litanti; Ade Dwi Lestari (Jurnal Akta Trimedika, 2024)
Pterygium is an eye condition characterized by the growth of fibrous vascular tissue extending from the conjunctiva to the cornea. Various environmental factors such as dust, UV exposure, and dry air contribute to its development. A 33-year-old male worker at a mining company presented with complaints of red eyes for the past six months. The clinical diagnosis of the patient was bilateral pterygium. The patient has worked for 11 years as an administrative officer at a dusty coal mining company, but UV exposure during work trips without eye protection, computer exposure, and air conditioning are more significant for this worker. Based on the 7-step occupational diagnosis, it was concluded that the pterygium is not directly related to his job. Control measures need to be implemented to reduce further risk.